Development and validation of a rapid, generic measure of disease control from the patient's perspective: the IBD-Control questionnaire. Issue 7 (9th October 2013) - Bodger, Keith; Ormerod, Clare; Shackcloth, Daniela; Harrison, Melanie; ,
Abstract : Introduction: The use of patient reported outcome measures to support routine inflammatory bowel disease (IBD) care is not widespread and suggests that existing questionnaires lack relevance to day-to-day decisions or are too cumbersome to administer. We developed a simple, generic tool for capturing disease control from the patient's perspective to address these barriers. Methods: Development based on literature review, patient focus groups/interviews and a steering group, defining a limited set of generic questions. The 'IBD-Control' questionnaire comprises 13 items plus a visual analogue scale (VAS) (0–100). Prospective validation involved baseline completion of IBD-Control, quality of life (QoL) questionnaire (UK-IBD-Q), EuroQol (EQ-5D), Hospital Anxiety and Depression Score; and clinician assessment (blinded to questionnaire; recording Harvey-Bradshaw Index or Simple Clinical Colitis Activity Index; Global Clinician Rating; treatment outcome). Results: 299 patients returned baseline surveys (Crohn's disease, n=160; ulcerative colitis, n=139) and 138 attended for repeat visits. Completion time (mean; SD): 1 min 15 s; 25 s; Internal consistency : Cronbach's α for all 13 items (0.85); for subgroup of eight questions ('IBD-Control-8'; 0.86). Strong correlation between IBD-Control-8 and IBD-Control-VAS (r=0.81). Test-retest reliability (2 week repeat): intra-class correlation=0.97 for IBD-Control-8 and 0.96 for IBD-Control-VAS. Construct validity : Moderate-to-strong correlations between IBD-Control-8 and IBD-Control-VAS versus activity indices, UK-IBD-Q and EQ-5D (utility) with r values 0.52–0.86. Discriminant validity (mean instrument scores for remission, mild, moderate or severe): p<0.001 (analysis of variance (ANOVA)). Sensitivity to change : Effect sizes: 0.76–1.44. Conclusions: The IBD-Control is a rapid, reliable, valid and sensitive instrument for measuring overall disease control from the patient's perspective. Unlike existing patient reported outcome measures, its simplicity, ease-of-use and generic applicability make it a candidate for supporting routine care.